Role of Misoprostol in Induction of Labor: Sublingual versus Vaginal in Tikrit City - Tahir Saihood, Sumaya (Tikrit Journal of Pharmaceutical Sciences, 2023)
A successful induction of labor leads to vaginal delivery of a healthy baby, in an acceptable time frame with minimum maternal discomfort or side effects. To compare the efficacy and safety of sublingual and per vaginal 25µg misoprostol for labor induction. Primary outcome measures were the number of cases delivering vaginally, Secondary requirement, the incidence of meconium-stained liquor, number of cesarean deliveries, the incidence of hyperstimulation/tachysystole, maternal adverse effects and neonatal outcomes. A prospective study was conducted in Tikrit Teaching Hospital. Indications were reviewed; 416 women randomly received misoprostol 25 µg vaginally and sublingually every three hourly for maximum three doses. Outcomes were analyzed accordingly. The number of the cases who successfully delivered vaginally was greater in the sublingual group. The induction to vaginal delivery interval was significantly shorter in sublingual group. The incidence of tachysystole and meconium-stained liquor were more in the vaginal than in the sublingual group. The mean doses, mode of delivery, oxytocin augmentation and maternal outcomes were significantly favorable in sublingual group. No significant difference is seen in neonatal outcome. Sublingual misoprostol 25 µg administered three hourly for labor induction has better effficacy as compared to 25 µg of vaginal misoprostol.